Pengaruh Terapi Individu Generalis dengan Pendekatan Strategi Pelaksanaan Komunikasi Terhadap Frekuensi Halusinasi pada Pasien Halusinasi: The Influence of Generalist Individual Therapy with a Communication Strategy Implementation Approach on the Frequency of Hallucinations in Patients with Hallucinations - Wan Muharyati; Esi Afriyanti; Adelse Prima Mulya (NERS Jurnal Keperawatan, 2012)
One of the non-pharmacological therapies that can be used to reduce the frequency of hallucinations is general individual therapy by the implementation of communication strategies. The purpose of this study was to determine the effect of general individual therapy in reducing the frequency of hallucinations of patients at RSJ. H.B Saanin Padang. This study used a quasi-experimental design in one group (one group pre-test - post-test design). Sampling was done by purposive sampling. The samples of this study consisted of 13 people. Samples were provided with individual therapy using the implementation of communication strategy approach for 14 days. After that, samples were measured with regular interviews. This data was then analyzed using the Wilcoxon test with a 95% degree of confidence. Wilcoxon test results obtained p-value = 0.001. This result showed that the individual therapy approach to the implementation of communication strategies was effective in reducing the frequency of hallucinations of patients with hallucinations in the psychiatric hospital H.B Saanin Padang.